Pengaruh Efisiensi Transaksi Dan Keamanan Pembayaran Digital Berbasis Qris Terhadap Peningkatan Pendapatan UMKM Ritel Di Kota Bengkulu - Anni Faiza Kamila; Apsifa Lintang Kirana; Candra Salim; Joko Kurniawan; Meuthia Rinjani Khairunnisha (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the effect of transaction efficiency and digital payment security based on QRIS on the income improvement of retail MSMEs in Bengkulu City. This research uses a quantitative approach with an associative method. Data were collected through questionnaires distributed to retail MSMEs using QRIS in Bengkulu City using purposive sampling technique. Data analysis was performed using multiple linear regression with SPSS. The results show that transaction efficiency has a positive and significant effect on MSME income improvement. Digital payment security also has a positive and significant effect on MSME income improvement. Simultaneously, transaction efficiency and digital payment security significantly affect MSME income improvement in Bengkulu City. These findings support Transaction Cost Theory, Technology Acceptance Model, Trust Theory, and Resource-Based View in explaining how QRIS adoption contributes to MSME performance. This study contributes to the literature on digital payment adoption and MSME development in Indonesia.